Cosmetic manufacturers readiness to implement halal certification by investigating the effects of top management support and knowledge management process - Zulkifli, Nur Syazana (2021)
As the top scorer of Global Islamic Economy Indicator (GIEI), Malaysia plays an important role to capture the fast-changing demand for halal industry products and services, including halal cosmetic. This phenomenon has created vast opportunities for cosmetic manufacturers to implement Halal Certification as a strategic move. Most previous researches on Halal Certification have focused on food industry, thus understanding on halal cosmetics industry remain sparse. The main purpose of this study is to investigate the readiness of cosmetic manufacturers in Malaysia to implement Halal Certification. Specifically, this study investigates the influence of the external factors like government pressure, government support, supplier pressure, customer pressure and competitor pressure towards firm’s readiness to implement Halal Certification. This study also incorporates top management behaviour and knowledge management process for mediation and moderation effect respectively. This study employs an Institutional Theory, Theory of Planned Behaviour (TPB) as well as the Resource-Based View Theory (RBV) to explain the interlinkages. Based on 143 usable responses from the cosmetics manufacturers, the Statistical Package for the Social Sciences (SPSS) and the Partial Least Square (PLS) are applied to test the proposed hypotheses. Overall, all six dimensions of readiness to implement Halal Certification developed were strongly associated with the degree of organizational readiness for the adoption of Halal Certification in their cosmetics business operations. The results show that institutional pressure and top management behaviour (as mediator) are positively related to the organizational readiness to implement Halal Certification. However, the relationship between knowledge management process and organizational readiness to implement Halal Certification is found to be insignificant. Information in this study is beneficial to assist top management in cosmetics industry to increase their efforts toward best practises in order to implement Halal Certification in the future and stay competitive in the market, particularly in Malaysia.